(untitled) (Al-Academy, 2022)
The study aims to integrate the visually impaired people into the art connoisseur community through producing special print artworks to enable the visually impaired people to use their other senses to feel artworks by using artistic printing techniques through adding some prominent materials to the printing colors or making an impact that visually impaired people can perceive using their other senses. This study also aims to set up art exhibitions that display tangible works that can enable visually impaired people to feel artwork and understand its elements to enable them to feel it through other senses.The study follows the experimental method, through using artistic printing techniques, which allow printing with prominent textures that enable visually impaired people to utilize their senses to perceive and savor artistic prints